Experience of Analysis and Synthesis of Contextual Meanings of the Dominant Unit child in Poetic Text by W. Blake “The Lamb”: Intertextual Aspect - I. V. Sergodeev (Научный диалог, 2020)
The article is devoted to the study of the dynamics of the semantic complex of dominant units of a poetic text. A dominant unit is interpreted as a token that can be defined by dictionary and non-dictionary, figurative, author’s meanings in a given work context due to its intertextual connections with units of address texts. It is noted that the dominant unit is a unit of intertextuality. The relevance of the study is in the insufficient knowledge of the processes of organizing the semantic complex of text units and the poetic text as a whole. The object is a poetic text, namely the poem of the English poet W. Blake “The Lamb” (the original text of the work is provided with interlinear translation). The subject is the dominant unit child of a given poetic text. The methodology of the article is based on the theory of intertextuality. A typology of intertextual relations is given: auto-, in-, para-, architextuality. The concepts of intertextuality and intercontextuality are differentiated. The concept of prototext is considered. A model for the analysis and synthesis of dominant units contextual meanings of a poetic text is proposed. The model is divided into five stages: fragmentation of the work under consideration, allocation of the analysis unit and its context analysis, establishment of identical analysis units in address texts, context analysis of address texts and their units, synthesis of the obtained context values.